Analisis Yuridis Kebaruan Perlindungan Tenaga Kerja Kesehatan Ditinjau Berdasarkan Undang-Undang Nomor 17 Tahun 2023 - Muhammad Kamarulzaman Satria; Hudi Yusuf (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
The Law Number 17 of 2023 on Health brings about a significant change in the protection of healthcare workers in Indonesia. The background to the formation of this law is based on the need for broader and integrated protection for healthcare workers, in line with the mandate of the 1945 Constitution of the Republic of Indonesia and the challenges faced in providing quality healthcare services. This study uses a qualitative method with a normative juridical approach to analyze changes in the provisions of protection for healthcare workers based on Law Number 17 of 2023. The results of this study show that Law Number 17 of 2023 emphasizes compliance of healthcare workers with professional standards and ethics, and adds new rights such as wages, performance bonuses, health insurance, and opportunities for self-development. However, there are several issues that arise, notably the ambiguity in Article 462 paragraph 1 which regulates criminal sanctions for healthcare workers' negligence. This clearly threatens the continuity of protection for healthcare workers and indicates a lack of legal certainty in the law. In conclusion, while Law Number 17 of 2023 has brought about significant changes in the protection of healthcare workers, further revisions and improvements are still needed to ensure optimal protection and legal certainty for healthcare workers in Indonesia.